Language-literature integration in high-school EFL education: investigating students' perspectives. Issue 4 (7th August 2020) - Viana, Vander; Zyngier, Sonia
ABSTRACT: The use of literature in English as a Foreign Language (EFL) environments has had a long and controversial history. Currently, literature has returned to the language classroom once similarities between literary texts and everyday communication have been identified. However, literature is generally approached in a reductionist way in which students are expected to extract information from texts rather than experience them. The workshop investigated here innovates by engaging students in meaningful aesthetic creations. Our study contributes to research on an under-investigated topic, namely, the integration of literature in EFL education in a high-school context. It analyzes Brazilian students' perceived learning/teaching gains/losses empirically after their completion of a language-literature integrated workshop unit on iconicity. The findings of this rigorous bottom-up analysis show students' positive attitude, particularly regarding the teaching strategies, creative (or otherwise) exercises proposed, life and educational relevance of the workshop, and content/language learning. This article provides original empirical ground for the integration of language and literature in high-school EFL education, which stimulates autonomy and moves away from approaches where students tend to repeat interpretations validated by teachers or critics. Its significance expands beyond the focal country given that the improvement of students' literacy is a major need observed in several countries (e.g. United Nation's fourth development goal on 'quality education').